Type-A Thymoma: A Case Report - Hermawan, Yosua Kevin; Yaniswari, Ni Made Dwita (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Thymoma is a neoplasm that arises from the thymus gland. Around one-third of the patients are asymptomatic. Five subtypes of thymoma differentiate from the cell’s morphology based on the World Health Organization (WHO). Type-A thymoma comprises oval or spindle epithelial cells.Case: We presented a 49-year-old woman with a persistent cough and shortness of breath when performing heavy tasks. Chest radiography showed opacity on the mediastinum. Chest computed tomography with contrast revealed a tumor in the anterior part of the mediastinum and pericardial effusion. The patient underwent an Ultrasonography (USG) guided transthoracic needle aspiration (TTNA) and the histopathology examination showed a type-A thymoma. The patient was referred to a cardiothoracic surgeon for further management.Discussion: Type-A thymoma has a good prognosis and is rarely associated with myasthenia gravis. It has a less malignant nature compared to type B2 thymoma. However, it still can cause respiratory problems through the mass effect of the tumor itself. Surgery is usually the treatment of choice. Radiotherapy and chemotherapy can also be considered if complete resection is hard to achieve.Conclusion: Type-A thymoma has a less malignant nature and has a good prognosis. In this case, the tumor caused compression into the right lung resulting in the partial collapse of the right middle lobe and pericardial invasion were taken into consideration due to pericardial effusion.